Estudo das características biomecânicas e estratégias do controle neuromuscular de adultos jovens com paralisia cerebral do tipo discinético durante atividade de membro superior - Barcala, Luciana (2018)
The diskynetic type of cerebral palsy affects 15% to 20% of the patients diagnosed with cerebral palsy. The cerebral palsy is the most common cause of the motor deficiency. The motor impairment generates involuntary and sustained muscles contractions that results in torsion movements, repetitive movements and abnormal posture that consequently promote limitations on the daily life activities. The movement analysis through the kinematic and electromyography together can detect relevant alterations of the neuromuscular system during the functional activity what guides a better treatment in the rehabilitation process, since it has as the main goal the functional independency. Clinically, the use of loads in functional trainings is fundamental to improve stability and control over the undesirable movements of the upper limbs. However, there are no evidences about the effects of the use of loads on the upper limbs movements, nor how much weight is good to be used to reach the satisfactory results during the rehabilitation. Even though the use of loads is a resource that promotes more improvements on the functionality, nothing is known about the neuromuscular modifications that occur during this intervention. The task of drinking was analyzed in three phases: the going, the adjustment and the return. According to this questioning, this thesis was divided in two studies that had two aims: 1) Compare the electromyographic activity and the range of movement of the dominant upper limb during a daily functional activity of drinking water with a mug between young adult patients with diskynetic cerebral palsy and young healthy adults; 2) Analyse and compare the muscular co-activation during the same daily functional activity of drinking water with a mug in both young healthy adults and young adult patients with diskynetic cerebral palsy and the interference of the use of the loads on the diskynetic people of this sample. The sample was composed by 30 young adults of both genders, who were divided in two groups: diskynetic (GD; n=15) and control (GC; n =15). The study 1 showed a lower electromyographic activity of the anterior deltoid, posterior deltoid and biceps brachii in the GD during the execution of the task in comparison with the GC. According the analyses of the interaction between the groups and the phases, only the biceps brachii showed lower activity during the outward and adjustment phases in comparison with the GC. In relation of the range of movement (ROM), the GD showed lower ROM for the shoulder, elbow, forearm and wrist movements, where the interaction between groups and phases, the GD showed lower ROM for flexion and internal rotation of shoulder, elbow flexion, forearm pronation and ulnar deviation during the outward phases, and lower ROM for shoulder extension and external rotation, elbow extension, forearm supination and radial deviation during the inward phase. The study 2 compared the muscular co-activation between the GD and GC, while the GD showed higher level of muscles co-activation of shoulder and elbow during the outward phase; shoulder, elbow and wrist in the adjustment phase, and elbow in the inward phase. Also, it was verified in the GD that the loads usage did not interfere in the muscular co-activations (p>0,05). The results of this thesis contribute to a better understanding of the functional movements of PCD patients. The interpretation of the results can be utilized to guide the assessment and the process of rehabilitation, since the important components of the motor control were shown.